2018
DOI: 10.1111/jfbc.12730
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/sodium tripolyphosphate nanoparticles as efficient vehicles for enhancing the cellular uptake of fish-derived peptide

Abstract: Methodology to enhance the intestinal absorption of peptides is an important challenge due to their easily degradation and poor permeability across the intestinal epithelium. In this study, the fish‐derived peptide (DGDDGEAGKIG)‐loaded chitosan (CS) nanoparticles (CS/PEP‐NPs) were prepared and investigated in Caco‐2 monolayer model. The results indicated zeta potential of CS/PEP‐NPs increased with the increase in molecular weight of CS (10–50 kDa). Transmission electron microscopy images revealed the CS/PEP‐NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
3
1
0
Order By: Relevance
“…Therefore, it proves that they did not conjugate to the nanoparticle, instead they were encapsulated. In addition, the zeta potentials of PCNPs were almost similar with reported studies, which were in the range of +20 mV to +30 mV [46,64,65]. Moreover, the positively charged PCNPs could provide better interaction with negatively charged mucosal membrane; this could later facilitate the PCNPs delivery and cellular uptake [46,66].…”
Section: Particle Size Distribution By Zetasizersupporting
confidence: 84%
“…Therefore, it proves that they did not conjugate to the nanoparticle, instead they were encapsulated. In addition, the zeta potentials of PCNPs were almost similar with reported studies, which were in the range of +20 mV to +30 mV [46,64,65]. Moreover, the positively charged PCNPs could provide better interaction with negatively charged mucosal membrane; this could later facilitate the PCNPs delivery and cellular uptake [46,66].…”
Section: Particle Size Distribution By Zetasizersupporting
confidence: 84%
“…However, the sample CNPH showed structural differences inside of each nanoparticle ( Figure 3 B), which could indicate that the FPH was well integrated within the chitosan network. Similar morphological characteristics were demonstrated by Zhao et al [ 51 ] for chitosan/TPP nanoparticles loaded with fish-derived peptides using chitosan with a molecular weight of 150 kDa and a 90–95% degree of deacetylation.…”
Section: Resultssupporting
confidence: 84%
“…3B), which could indicate that the FPH was well integrated within the chitosan network. Similar morphological characteristics were demonstrated by Zhao et al [51] for chitosan/TPP nanoparticles Previous studies have reported ACE-inhibitory activity for chitosan nanoparticles [44,45]. However, the mechanism involved in the ACE-inhibitory activity of polysaccharides is unknown [46].…”
Section: Morphology Of Nanoparticlessupporting
confidence: 83%
“…Chitosan nanoparticles (CNPs) were prepared by an ionic gelation method, which involves the crosslinking reaction of the positively charged CS and negatively charged TPP. [26][27][28][29][30][31] First, ∼1.0 mL of 1.0% acetic acid was added to the low-molecular weight CS to dissolve it and then further diluted to form a working solution concentration of 0.5 mg mL −1 CS. Next, the pH of the CS was adjusted to 5.0 by adding a 1 M aqueous sodium hydroxide solution.…”
Section: Preparation Of Nanoparticle Samplesmentioning
confidence: 99%